2022
DOI: 10.3390/f13101628
|View full text |Cite
|
Sign up to set email alerts
|

Increased Soil Bacterial Abundance but Decreased Bacterial Diversity and Shifted Bacterial Community Composition Following Secondary Succession of Old-Field

Abstract: Plant secondary succession is a very effective approach for the rejuvenation of degraded ecosystems. In order to comprehend alterations and driving mechanisms of soil bacterial communities under secondary succession of old-field and reveal their subsequent impacts on the decomposition and accumulation of soil organic carbon (SOC) and nitrogen (SON), we investigated changes in soil bacterial communities following ~160 years of old-field succession on the Loess Plateau of China through analyses of quantitative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 87 publications
(161 reference statements)
1
0
0
Order By: Relevance
“…In this study, it was found that the dominant phylum of bacteria in vegetable land, wasteland, woodland, and cultivated land was Proteobacteria, with a relative abundance of 20.69% to 32.70%. This result is consistent with Yang Wen et al, who found that Proteobacteria were the dominant bacteria in the soil after succession of old fields in the Loess Plateau of China [39]. Proteobacteria are mostly facultative or aerobic bacteria, which are widely distributed and have strong adaptability to the environment.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, it was found that the dominant phylum of bacteria in vegetable land, wasteland, woodland, and cultivated land was Proteobacteria, with a relative abundance of 20.69% to 32.70%. This result is consistent with Yang Wen et al, who found that Proteobacteria were the dominant bacteria in the soil after succession of old fields in the Loess Plateau of China [39]. Proteobacteria are mostly facultative or aerobic bacteria, which are widely distributed and have strong adaptability to the environment.…”
Section: Discussionsupporting
confidence: 91%